2019
DOI: 10.1158/0008-5472.can-19-0542
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the High-Mobility Group Box 3 Protein Sensitizes Chemoresistant Ovarian Cancer Cells to Cisplatin

Abstract: Chemotherapeutic regimens for ovarian cancer often include the use of DNA interstrand crosslink-inducing agents (e.g., platinum drugs) or DNA double-strand break-inducing agents. Unfortunately, the majority of patients fail to maintain a durable response to treatment, in part, due to drug resistance, contributing to a poor survival rate. In this study, we report that cisplatin sensitivity can be restored in cisplatin-resistant ovarian cancer cells by targeting the chromatin-associated high-mobility group box 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
0
33
1
Order By: Relevance
“…HMGB3 can bind to DNA and bend it 45 . Mukherjee et al 46 reported that HMGB3 promotes DNA damage through the ATR/CHK1/p-CHK1 signalling pathway. Moreover, micronuclei contain not only proteins, but also genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB3 can bind to DNA and bend it 45 . Mukherjee et al 46 reported that HMGB3 promotes DNA damage through the ATR/CHK1/p-CHK1 signalling pathway. Moreover, micronuclei contain not only proteins, but also genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, HMGB1 and HMGB2 facilitate V(D)J recombination by enhance the affinity of the RAG complexes for DNA and increased the cleavage effectiveness [40,41]. Inhibition of HMGB3 in cisplatin-resistant ovarian cancer cells resulted in transcriptional downregulation of ATR and CHK1, subsequently attenuating the ATR/ CHK1/p-CHK1 DNA damage signalling pathway [19]. In our study, we found that down-regulation of HMGB3 significantly impaired the radiation-induced DNA damage repair and increased cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB3 has 80% identity with HMGB 1, 2 and may share some functions with them [17]. Previous studies revealed that HMGB3could promote tumor development and maintain dedifferentiation in urinary bladder cancer, oesophageal squamous cancer, gastric cancer, non-small cell lung cancer, breast cancer and hematopathy [18][19][20][21]. Nevertheless, there has not yet been a report about the biological function of HMGB3 in regulating cervical cancer radioresistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functions of most of the genes in our signatures have not been entirely elucidated. For genes associated with OS, the chromatin-associated high-mobility group box 3 (HMGB3) protein is upregulated and has poor prognosis, and its targeted depletion can attenuate cisplatin resistance in human OC cells ( Mukherjee et al, 2019 ). PYGB has been shown to be upregulated in OC tissue and markedly associated with poor prognosis in OC patients ( Zhou, Jin & Wang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%